Predictors of teachers’ perceived assessment skills and assessment practices in public universities of Ethiopia [version 1; peer review: 1 approved, 2 approved with reservations] - Menna Agago; Million Wolde; Samuel Zinabu (Routledge Open Research)
Background Assessment is an integral component of learning at higher education institutions of Ethiopia. It plays a critical role of ensuring quality education and student learning and development. In this respect, teachers’ capabilities to conduct effective assessment and use assessment evidence are central to quality assessment practices. These capabilities are related to different attributes such as their academic levels, teaching experience, assessment training received and specializations. Therefore, this study aimed to examine predictors of teachers’ perceived assessment skills and assessment practices in public universities of Ethiopia. Methods Assessment Practices Inventory was adopted and distributed to a sample of 380 randomly selected teachers from four randomly selected public universities of Ethiopia. 355 properly completed questionnaires were used for analysis. Teachers’ academic level, teaching experience, field of specialization and assessment training were included in two separate multiple regression analyses. Results Academic level (p < 0.001), teaching experience (p < 0.001), and assessment training (p < 0.001), were significantly positively related to both teachers’ perceived assessment skills and assessment practices. Teachers’ perceived assessment skill was also strongly correlated with their assessment practices. Field of specialization was not significantly correlated to both teachers’ perceived assessment skills and assessment practices. Conclusions The study concluded that academic level of teachers, their teaching experience, and assessment training they received predict their perceived assessment skills and assessment practices. Appropriate assessment training and professional development programs should be devised based on the higher education curriculum needs and teachers’ actual gaps in assessment. Teacher education programs would benefit from the findings of this study to carefully devise their programs to fulfill the growing needs of learning and assessment.